La cultura jama coaque: los diseños como motivo gestor para una propuesta pictórica contemporánea - Arevalo Ordoñez, Paul Ricardo (2019)
The research work "THE JAMA-COAQUE CULTURE: DESIGNS AS A MANAGEMENT REASON FOR A CONTEMPORARY PICTORIC PROPOSAL" has been developed in the province of Manabí precisely in the city of Jama del Cantón with the same name. The study presents an analysis of the designs of this culture, which constitute true artistic manifestations, the product of a whole cultural legacy that the beings of yesteryear created and transmitted. The symbolic richness provided by pre-Hispanic cultures in Ecuador is the clearest evidence that man developed a very particular worldview, the same that allows it to be recognized in a unique way. From the wonderful and extensive Jama-Coaque world, the most pertinent information has been recorded to understand its worldview, very valuable designs and symbols that have been an important reference to make pictorial works and revalue the most representative of this culture and its enigmatic past